Birth Certificate as a Manifestation of Personal Identity - Denny Setya; Aden Warliman; Nursahidin, Nursahidin; Dian Andriany (PT FORMOSA CENDEKIA GLOBAL, 2024)
Based on the background that has been presented, the researcher wants to evaluate the effectiveness of the birth certificate making process at the Population and Civil Registration Office of Kuningan Regency, especially in terms of service speed and community satisfaction. This research uses a qualitative approach by involving key informants such as the Head of Civil Registration Division, Reni Sriherliyani, SE, M.M., and the Head of Civil Registration Section, Teti Tresnawati, SE. The results of the interview show that the process of making a birth certificate at the Population and Civil Registration Office of Kuningan Regency has been carried out in accordance with applicable legal provisions, including Law Number 24 of 2013 concerning Amendments to Law Number 23 of 2006 concerning Population Administration, as well as Regional Regulation Number 1 of 2015 concerning Amendments to Kuningan Regency Regional Regulation Number 3 of 2010 concerning Population Administration Services. The author concludes that the service of making birth certificates at the Population and Civil Registration Office has been effective, with an emphasis on achieving concrete time and in accordance with applicable legal provisions. Nevertheless, there are still some obstacles in the process of making birth certificates at the Office.